Value chain promotion and the role of Social Capital in Ecuador : an illustrative study - Hebets, Jennifer (2009)
In the following investigation I seek to consider one particular program which has sought to promote Local Economic Development through strengthening of a local value chain. The program has been implemented through the efforts of the United States Agency for International Development and utilizes market-based strategies. Through an in-depth analysis of the program I seek, specifically, to understand the role of social capital. Ultimately, this investigation seeks to answer the question: Does social capital play a significant role on the local level in value chain and cluster poverty-reduction programs? Through a close analysis of this program funded by the United States Agency for International Development in a historically, economically and culturallu dynamic regions of the country; we will have the opportunity to understand in-depth a program aimed at increasing incomes for local producers using market-based strategies.